Factors Causing Expired Medicine in Puskesmas Cendrawasih Makassar City - Hasyim, Muhammad Farid; Roosevelt, Alfreds; Enriana, Irma (Jurnal Farmasi Sandi Karsa, 2022)
Pharmaceutical services carried out at the (community health centers are one of the efforts to improve the quality of health services for the community. This pharmaceutical service can be supported by good drug management, which is expected to prevent and overcome drug problems, such as problems with expired drug stocks. This problem can cause losses for the Community health centers and the government. This study aims to identify drug management, and determine the factors that cause expired drugs at Cendrawasih Health Center Makassar City. This type of research is a qualitative research. Data were obtained by conducting interviews with an informant and observing and reviewing expired drug stock documents. The results of the study obtained that there were 20 types of drugs that expired from January to June 2021. The causes of expired drugs were the time the drug was brought to the health center close to the drug expiration time, errors in the planning process to distribution of drugs outside the health center for unknown causes so the number of drugs that arrived at the Cendrawasih Health Center did not match the needs, the Covid-19 pandemic caused the community health centers to not be able to carry out counseling and distribution of drugs optimally. The conclusion of this study is that the implementation of drug management at the Cendrawasih Health Center has gone well but has not been maximized, besides that factors from outside the community health centers and the Covid-19 pandemic are also factors that cause expired drug stocks.